2016
DOI: 10.1016/j.ijsolstr.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent elastic and elasto-plastic cohesive zone models for dynamic crack propagation

Abstract: To overcome deficiencies with existing approaches a new cohesive zone model is introduced and trialled in this paper. The focus is on rate-dependent cohesive zone models which have appeared in the recent literature but can be shown to suffer unrealistic behaviour. Different combinations of material response are examined with rate effects appearing either in the bulk material or localised to the cohesive zone or in both. A benefit of using a cohesive-zone approach is the ability to capture plasticity and rate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…From the results shown in Figures 11 and 12, it can be concluded that any value higher than 6 for the updates parameter N u provides satisfactory results with a significant reduction in computational cost. It is clear from Figure 11 that the predicted results are reasonably close to each other for values of N u set to (56,28,14,7), which correspond to ΔN ≈ (100, 200, 400, 800), respectively. Differences are more noticeable however for values of N u lower than 6, where N u = 3 corresponds to ΔN≈2000 and N u = 1 corresponding to ΔN≈5600, as shown in Figure 12.…”
Section: Fast-track Effect On Accuracy Of the Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From the results shown in Figures 11 and 12, it can be concluded that any value higher than 6 for the updates parameter N u provides satisfactory results with a significant reduction in computational cost. It is clear from Figure 11 that the predicted results are reasonably close to each other for values of N u set to (56,28,14,7), which correspond to ΔN ≈ (100, 200, 400, 800), respectively. Differences are more noticeable however for values of N u lower than 6, where N u = 3 corresponds to ΔN≈2000 and N u = 1 corresponding to ΔN≈5600, as shown in Figure 12.…”
Section: Fast-track Effect On Accuracy Of the Resultsmentioning
confidence: 53%
“…The effect of the tractionseparation law shape is discussed in Tvergaard and Hutchinson, 27 where it is concluded that the shape of the law does not significantly affect the analysis results. However, it is shown in previous studies 28,[30][31][32] that the TSL has an effect on fracture behaviour but the significance of this effect depends on geometry and material properties.…”
Section: Cohesive Zone Model For Fatiguementioning
confidence: 99%
“…It also allows to introduce interesting physical mechanisms into the fracture model through the use of different kind of traction-separation laws and the energy dissipation rate can be controlled very accurately. These traction-separation laws can include rate effects (Salih et al (2016)), account for stress triaxiality ratio (Banerjee and Manivasagam (2009)) and fatigue effects (Nguyen et al (2001)), among others.…”
Section: General Remarksmentioning
confidence: 99%
“…A few studies were conducted to understand the feasibility of existing cohesive models in delamination studies of composite interfaces [29][30][31]. May et al [29] identified the necessary of considering simultaneously the rate effect of interface strength and fracture toughness, through the comparison study of four different cohesive models for the impact simulation of composites.…”
Section: Introductionmentioning
confidence: 99%